Challenges in assisting labour trafficking and exploitation victims in Spain - Villacampa Estiarte, Carolina (International journal of law, crime and justice, 2022)
Labour trafficking and exploitation remain an understudied criminal reality in academia, particularly those aspects most linked to a victim-centric approach to it, such as victim assistance. To identify the challenges faced by victim service providers when dealing with these victims, a qualitative study was undertaken in Spain consisting of 34 indepth interviews with professionals who had provided assistance in these cases. Based on the premise that victim assistance is a continuum, shortcomings are identified in three main areas and proposals are made to overcome them. The first one is victim detection and identification, hindered by some professionals’ biases, lack of training, and the rigidity and non-systematic nature of the identification system. The second one is the intervention programme, which is not specific to these victims and lacks economic and residential resources and a referral circuit. The third area is reparation, with challenges at the economic and intangible levels.